Physical and damping properties of kenaf fibre filled natural rubber/thermoplastic polyurethane composites - A.M., Noor Azammi; Salit, Mohd Sapuan; Ishak, Mohamad Ridzwan; Hameed Sultan, Mohamed Thariq (Elsevier, 2020)
The paper presents the investigation of the effect of alkaline treatment of sodium hydroxide (NaOH) on physical and dynamic mechanical analysis (DMA) viscoelastic properties of kenaf fibre filled natural rubber (NR)/thermoplastic polyurethane (TPU) composites. The treated kenaf fiber, NR and TPU were weighed and proportioned according to the required compositions and were blended using hot mixed Brabender machine. The polymer composites were then fabricated using the hot press to form a sample board. The sample was cut and prepared and water absorption, density, thickness swelling and DMA tests were performed. As far as physical properties are concerned, composites with the highest NR amount of shows the best results, which indicates good fiber bonding adhesion. The polymer composites with the highest amount of TPU shows the highest damping properties at high temperature.